PENGARUH UKURAN PERUSAHAAN, STRUKTUR FINANSIAL DAN PERTUMBUHAN JUMLAH NASABAH KREDIT PADA PROFITABILITAS - Koriawan, Wirawati, Made Ucca Pavitrin (E-Jurnal Akuntansi, 2014)
The current rural economic activity has grown by leaps and bounds. In line with the development of economic activities, transactions between parties who have surplus funds and the lack of funds that will become easier with the presence of intermediaries, known as financial institutions, one of which is the Village Credit Institutions (LPD). This study aimed to determine the effect of firm size, financial structure and increase the number of credit customers to Profitability LPD Buleleng Regency Period 2009-2012 In order to answer these problems this study used 160 samples of data and data analysis techniques, namely multiple linear regression. From the test results it is known that the size of the company and financial structures affect the profitability of LPD in Buleleng regency, while the increase in the number of credit customers had no effect on the profitability of LPD in Buleleng regency.
Keywords: company size; financial structure; custoer.